Lead time and productivity improvement in a pizza assembly process using lean manufacturing tools - Escudero, Bruce (2020)
The present work aims to improve the lead time and productivity in the pizza assembly process of a medium-sized company. To this end, lean manufacturing tools were used for implementing a work method that eliminates wastes or activities that add no value to the process. The results showed a reduction in the process lead time by 99% and an increase in the productivity of up to 20% compared to the initial situation. It was concluded that the tools used in the research, such as the line balancing graph, 5S or cellular manufacturing, allowed the elimination of wastes found during the process.